Interventions to reduce self-harm on in-patient wards: systematic review. Issue 3 (16th April 2021) - Nawaz, Rasanat Fatima; Reen, Gurpreet; Bloodworth, Natasha; Maughan, Daniel; Vincent, Charles
Abstract : Background: Incidents of self-harm are common on psychiatric wards. There are a wide variety of therapeutic, social and environmental interventions that have shown some promise in reducing self-harm in in-patient settings, but there is no consensus on the most appropriate means of reducing and managing self-harm during in-patient admissions. Aims: To review interventions used to reduce self-harm and suicide attempts on adolescent and adult psychiatric in-patient wards. Method: A systematic literature search was conducted between 14 March 2019 and 25 January 2021 using PsycINFO and Medline (PROSPERO ID: CRD42019129046). A total of 23 papers were identified for full review. Results: Interventions fell into two categories, therapeutic interventions given to individual patients and organisational interventions aimed at improving patient–staff communication and the overall ward milieu. Dialectical behaviour therapy was the most frequently implemented and effective therapeutic intervention, with seven of eight studies showing some benefit. Three of the six ward-based interventions reduced self-harm. Two studies that used a combined therapeutic and ward-based approach significantly reduced self-harm on the wards. The quality of the studies was highly variable, and some interventions were poorly described. There was no indication of harmful impact of any of the approaches reported in this review. Conclusions: A number of approaches show some promise in reducing self-harm, but the evidence is not strong enough to recommend any particular approach. Current evidence remains weak overall but provides a foundation for a more robust programme of research aimed at providing a more substantial evidence base for this neglected problem on wards.